Differences in the Anthropometric and Physiological Profiles of Hungarian Male Rowers of Various Age Categories, Rankings and Career Lengths: Selection Problems - Alfőldi, Zoltan; Borysławski, Krzysztof; Ihasz, Ferenc; Soós, Imre; Podstawski, Robert (Frontiers in Physiology, 2021)
Background: Little is known about the anthropometric and physiological profiles of lower-ranking athletes who aspire to rise to the pinnacle of their profession. Aim: The aim of this study was to create anthropometric and physiological profiles of Hungarian male rowers of different age categories (15–16, 17–18, and over 18 years), sports rankings and career lengths. Materials and Methods: Anthropometric and physiological profiles were created for 55 juniors, 52 older juniors and 23 seniors representing seven of the largest Hungarian rowing clubs. One-way independent analysis of variance (ANOVA) was used to compare arithmetic means. Results: Rowers in older age categories were significantly taller (185.0 ± 5.0 cm vs. 183.0 ± 7.3 cm vs. 178.7 ± 7.2 cm) and heavier (81.1 ± 8.8 kg vs. 73.7 ± 8.4 kg vs. 66.8 ± 12.3 kg) than their younger peers, with significantly higher BMI values and larger body dimensions. Compared to younger athletes, rowers in older age categories also covered 2,000 m significantly faster (6.6 ± 0.3 min vs. 6.9 ± 0.4 min vs. 7.5 ± 0.5 min) while developing significantly more power (372.2 ± 53.0 W vs. 326.8 ± 54.5 W vs. 250.6 ± 44.6 W). Similarly, seniors and older juniors had higher values of maximal oxygen uptake and force max (by 6.2 and 7.0 ml/kg/min, and by 263.4 and 169.8 N). Within the older juniors, internationally ranked rowers had significantly greater body height (+ 5.9 cm), body mass (+ 6.1 kg), sitting height (+ 2.7 cm), arm span (+ 7.9 cm), limb length (+ 3.73 cm) and body surface area (+ 0.21 m2). They also rowed 2,000 m significantly faster (–0.43 min, p < 0.001) and had significantly higher values of power (+ 58.3 W), relative power (+ 0.41 W/kg), jump height (+ 4.5 cm), speed max (+ 0.18 m/s) and force max (+ 163.22 N). Conclusion: The study demonstrated that potential differences in anthropometric and physiological profiles are more difficult to capture in non-elite rowers, and that the final outcome may be determined by external factors. Therefore, athletes with superior aptitude for rowing are more difficult to select from among lower-ranking rowers, and further research is needed to determine specific training requirements to achieve the maximum rowing performance.